KESETARAAN GENDER DITINJAU DARI SUDUT PANDANG NORMATIF DAN SOSIOLOGIS - Ismail, Zulkifli; Lestari, Melanie Pita; Rahayu, Panti; Eleanora, Fransiska Novita (SASI, 2020)
This study discusses that gender equality must be paired with justice and justice, between men and women must be equal and there must be no differences or contradictions. A normative study looking at it from the perspective of the following law is that submission will discuss the rights of a woman, everyone has equal rights without exception, and those rights have existed since man is in a supported reserve. Research methods using the normative juridical method by reviewing the literature and legislation, where the findings or results have met the requirements for the rights of everyone listed in the regulations of Law Number 39 of 1999, but viewed from the point of view seen sociological that in society assumes that gender equality can occur if each party considers to be responsible, their duties and roles. While the usefulness of this research provides benefits and participation of law enforcers, the community must not represent gender differences or injustice in the community, all people have the same rights, novelty in this study agrees and then gender in community life to prioritize and prioritize there will be the right to life, because that right is a very determined right granted to all people such as the right not to increase torture, get education, health, and eliminate the perception of gender inequality in any field or area of life, because everyone is the same and supports , in the field of law, and also government.